Sufistic Education in Adab Al-Mu’allimin: Eksplorasi Pemikiran Muhammad Ibn Sahnun - Kusdian, Iwan; Aziz, Ahmad Amir (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study aims to explore the values of sufistic education in Adab Al-Mu’allimin and the educational thught of Muhammad Ibn Sahnun. The research methoed employed is library research, focusing on classical texts and relevant literature. Data collection techniques involve an in-depth review of Adab Al-Mu’allimin and secondary sources discussing ibn sahnun’s thought and its sufistic contexxt. Data analysis is conducted through content analysis, identifying key themes and sufistic values presented in the text. The research findings indicate that Muhammad Ibn Sahnun integrates sufistic principles such as spiritual awareness, wisdom in teaching and character formation into educational methodology.these values include the importance of sincerity, concern for students, and ethical development. In conclutions, the sufistic approach in Adab Al-Mu’allimin emphasizes not only the transfer of knowledge but olso the formation of character and spirituality. The implications of this study highight the importance of applying sufistic values in modern education to produce holistic and principled educators.